Show Me a Perfect Teacher. Triangulation of Methods: Content Analysis of Focus Interviews and Analysis of Visual Materials Prepared by Students of Public Schools - Romanowska, Ewa Jurczyk; Kamila Gandecka (European Journal of Social Science Education and Research, 2015)
In 1912 Jan W?adys?aw Dawid published his idea of a teacher’s personality in Polish pedeutology in a book titled “O duszy nauczycielstwa” [“On the spirit of teaching”]. Therein he proposed that the decisive factor in the work of a teacher is substantial knowledge of psychology and pedagogics. In his idea of the “spirit of teaching” J.W. Dawid presented an image of a perfect teacher-educator, with the fundamental assumption that “in no occupation does the human factor have as high an importance as in teaching”. On the 100th anniversary of the dissemination of the conception research on the contemporary interpretation of the “spirit of teaching” and the perfect attitude of a teacher-educator was conducted. The research was carried out in Polish state schools, and the research subjects were students concluding a stage in their education (early school education, primary school, gymnasium, lyceum). The scientific investigation was conducted according to the interpretative paradigm and it was based on two methods: qualitative analysis of focus interviews and analysis of visual materials created by the research subjects. The paper presents conclusions drawn from the triangulation of the methods used in this research.